Cases and Materials in Company Law - Len Sealy, Sarah Worthington (Oxford University Press, 2013)
This volume covers all vital cases and combines sophisticated commentary with well-chosen notes and questions. This new edition retains the original successful structure and style, whilst being fully updated to reflect changes following the Companies Act 2006